Transformation of Traditional Housing in Traditional Village of Gunung Sari, Jatiluwih, Tabanan Regency - Dwijendra, Acwin; Putra, Diasana; ., Wirawibawa; Darma, Agus Surya (Journal of Civil Engineering, Architecture and Built Environment, 2020)
Traditional houses in Gunung Sari Pakraman Village, Jatiluwih Village, Tabanan, have a specific spatial configuration of traditional houses that becomes the local identity of the area. However, with the development of tourism in this village, traditional houses are not only a source of pride, but they also serve as an object of commodification. This is an interesting phenomenon in which on the one hand the people try to keep the identity of the traditional houses to attract tourists, while on the other hand they transform their houses into tourist accommodation facilities. Therefore, the aims of this study are to investigate the paradoxical phenomenon of the house transformation in this village; to find out what actually the design of the traditional vernacular house is; to explore the actual role and meaning of the transformed houses that can still be preserved; to find out the extent of the impact of the transformation and the factors causing such transformation; to explore the new roles and values that constitute the new configuration and discuss the impact of the new values on the meaning and values of the original configuration. Furthermore, this research will explore the differing aims that are to preserve the traditional house characteristics and to meet the tourism demands. Field observations were conducted at some houses selected by the stratified random sampling technique and interviews were carried out to explore the impact of the transformation of physical configuration on the values and meanings of traditional houses. With the identification of the characteristics of this transformation, it is expected that this study can be a reference on house transformation and provide a decent perspective for the community, government and tourism players on the transformation of traditional houses in Gunung Sari Pakraman Village, Jatiluwih Village, Tabanan. Keywords: houses, traditional, local identity, transformation, tourism.